Harmonic perturbations with delay of periodic separated variables differential equations - Bisconti, Luca; Spadini, Marco (Topological Methods in Nonlinear Analysis, 2015)
We study the structure of the set of harmonic solutions to perturbed, nonautonomous, T-periodic, separated variables ODEs on manifolds. The perturbing term, supposed to be T-periodic in time, is allowed to contain a finite delay. Our main result extends those of FS09 and spaSepVar but it cannot be simply deduced from them: It emerges from of a combination of the techniques exposed in those two papers.